2017
DOI: 10.1371/journal.pntd.0005898
|View full text |Cite
|
Sign up to set email alerts
|

Wide Distribution and Genetic Diversity of Babesia microti in Small Mammals from Yunnan Province, Southwestern China

Abstract: BackgroundBabesia, usually found in wild and domestic mammals worldwide, have recently been responsible for emerging malaria-like zoonosis in infected patients. Human B. microti infection has been identified in China, primarily in the Southwest along the Myanmar border but little direct surveillance of B. microti infection in rodents has been carried out here (Yunnan province). In this region, a diverse topographic range combined with tropical moisture sustains a high biodiversity of small mammals, which might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 14 publications
9
37
0
Order By: Relevance
“…Additionally, further consideration should be given for any patient exposures to certain ecological habitat types-specifically broad-leaved forest, shrub, and cropland-as this study has shown that such exposure is considered to be an important risk factor (Tables 3 and 4). Ecological habitat type of forest was also found to be an important risk factor for B. microti infection in other studies in Yunnan [26,27] and in Southeast Asia [28]. Thus, these findings show that forests, the natural habitat for ticks, likely represent areas of high risk for transmission of B. microti to humans, and as such, people either working in or traveling to the forest, should utilize adequate protection.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Additionally, further consideration should be given for any patient exposures to certain ecological habitat types-specifically broad-leaved forest, shrub, and cropland-as this study has shown that such exposure is considered to be an important risk factor (Tables 3 and 4). Ecological habitat type of forest was also found to be an important risk factor for B. microti infection in other studies in Yunnan [26,27] and in Southeast Asia [28]. Thus, these findings show that forests, the natural habitat for ticks, likely represent areas of high risk for transmission of B. microti to humans, and as such, people either working in or traveling to the forest, should utilize adequate protection.…”
Section: Discussionsupporting
confidence: 66%
“…Hence, the identification of U.S.-type in this study revealed the genetic diversity of B. microti in small mammals in Beijing, as well as that in China as a whole. Previously, the most highly recorded genotype of B. microti was the Kobe-type, including those recorded from Yunnan [26,27], Zhejiang, Fujian, and Taiwan [30,31]. Babesia microti of Ostu-type was also detected from Yunnan province [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Southeast Asian house rat, Rattus brunneusculus , was named by Hodgson in 1845. Although some scholars considered R. brunneusculus a synonym of the Asian house rat, R. tanezumi Temminck, 1844 ( Alfred, 2005 ; Ellerman, 1961 ; Wilson and Reeder, 2005 ), more scientists believe that R. brunneusculus is an independent rat species, which is obviously different from R. tanezumi in morphology ( Dhananjoy et al, 2014a , Dhananjoy et al, 2014b ; Gao et al, 2017 ; Wang, 2003 ). The Southeast Asian house rat is not only an important agricultural and forestry pest, but also an important reservoir host and infection source of some zoonoses (plague, HFRS, and scrub typhus, etc.)…”
Section: Introductionmentioning
confidence: 99%